Corporate lobbying and labor relations: Evidence from employee-level litigations - Unsal, Omer; Kabir Hassan, M.; Zirek, Duygu (Journal of Corporate Finance, 2017)
In this study, we analyze employee litigation and other work-related complaints to examine if the judicial process favors firms that engage in lobbying. We gather data for 27,794 employee lawsuits (after their initial court hearings) filed between 2000 and 2014 and test the relationship between employee allegations and firms' lobbying strategies. We find that employee litigation increases the number of labor-related bills in our sample. We document that an increase in employee lawsuits may drive firms into lobbying to change policy proposals. We also find robust evidence that case outcomes are different for lobbying firms compared to non-lobbying rivals, which may protect shareholder wealth in the long run. Our results suggest lobbying activities may make a significant difference in the effects of employee lawsuits. Our findings highlight the benefit of building political capital to obtain biased outcomes in favor of politically connected firms.